Edukasi Pengelolaan dan Pemilahan Sampah Organik serta Anorganik di Peserta Didik SDI Al Aziziyah - Fadhoni, Ajib Akhmad; Hakim, Banun Haidzir Amirul; Fitri, Lina Lutfiyah; Stevani, Oky Ayu (Indo-MathEdu Intellectuals Journal, 2025)
This study highlights the issue of waste in schools as a crucial issue affecting cleanliness, health, and the development of students' environmental stewardship. The subjects were students at SDI Al Aziziyah. A descriptive qualitative research method was used, with data collection techniques through observation and documentation. Data analysis was conducted descriptively, with the stages of data reduction, data presentation, and conclusion drawing. The results showed that most students were able to differentiate between organic and inorganic waste, but still had difficulty with mixed waste. The practice of sorting proved more effective than the lecture method because it increased students' enthusiasm, responsibility, and concern. The role of teachers as facilitators is crucial, while limited facilities and a lack of habituation at home were the main obstacles. These findings emphasize the need for synergy between schools, teachers, students, and parents to ensure a sustainable waste sorting culture that can be implemented in other schools.